2011
DOI: 10.3846/btp.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Combinations of Cash Flow Components to Predict Financial Distress

Abstract: Abstract. The aim of this research is to provide a model that predicts company's financial distress on the basis of the operational, investment and financing components of its cash flow statement. To prevent bankruptcy and its negative consequences that among them are abuse of creditors, investors, management and employees' right, the prediction of financial distress and its probable consequence such as bankruptcy is essential. To serve this purpose, for the research 70 reliable firm-years and 70 distressed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
1
20
0
17
Order By: Relevance
“…[9] found that bankruptcy is as a failure that occurs in a company that can be distinguished on the economic failures (economic distressed), and financial failure (financially distressed k. Janes [19] in his research on "Accruals, Financial Distress, And Debt Covenants" suggests that financial distress influenced by the performance of financial based on indicators of financial ratios. l. Kordestani et al [20] in his research on "Ability of Combinations of Cash Flow Components to Predict Financial Distress" suggests that financial distress influenced by the performance of financial-based on indicators of financial ratios. m. Elkamhi et al [21], in his research on "The cost of financial distress and the timing of default" suggests that financial distress influenced by financial and nonfinancial performance.…”
Section: Research Financial Distressmentioning
confidence: 99%
“…[9] found that bankruptcy is as a failure that occurs in a company that can be distinguished on the economic failures (economic distressed), and financial failure (financially distressed k. Janes [19] in his research on "Accruals, Financial Distress, And Debt Covenants" suggests that financial distress influenced by the performance of financial based on indicators of financial ratios. l. Kordestani et al [20] in his research on "Ability of Combinations of Cash Flow Components to Predict Financial Distress" suggests that financial distress influenced by the performance of financial-based on indicators of financial ratios. m. Elkamhi et al [21], in his research on "The cost of financial distress and the timing of default" suggests that financial distress influenced by financial and nonfinancial performance.…”
Section: Research Financial Distressmentioning
confidence: 99%
“…Some signs of financial difficulties include Increases in capital costs, more stringent requirements from creditors and suppliers for corporate financing, decreased cash flow, increased financial leverage and regular changes of key employees. These difficulties are caused by inefficient and ineffective operational system, deficiencies in market conditions such as recession and decline in market share and mismanagement of the company (Kordestani et al, 2011). Meanwhile, when the prediction of a company's financial distress is reliable, it provides a lot of benefits, such as the company managers taking corrective steps to avoid difficulties before bankruptcy occurs and investors understanding the profitability situation therefore, adjusting their investment strategies to reduce investment-related losses.…”
Section: Introductionmentioning
confidence: 99%
“…Berikut tahapan kebangkrutan yang dialami oleh beberapa perusahaan (Kordestani et al 2011 Model Altman (1983) Model ini dikembangkan oleh Edward I Altman pada 1968. Altman sukses dalam memprediksi kebangkrutan perusahaan dengan menggunakan multiple discriminant analysis dengan tingkat akurasi mencapai 95%.…”
Section: Kajian Teori Dan Pengembangan Hipotesis Analisis Kebangkrutanunclassified